The gospel of prosperity and its concept of development: A Ghanaian Pentecostal-Charismatic experience - Arthur, Justice A. (Religion, 2021)
The prosperity gospel, a doctrine in the global Pentecostal-Charismatic movement, characteristically demonstrates the nexus of the Christian faith and wealth. This article analyses Mensa Otabil, a Ghanaian prosperity preacher’s ‘20-year personal development plan’ for members of his church, the International Central Gospel Church (ICGC). It explores whether or not, why and how the members are aligning their lives and visions to his vision of how to achieve a better, prosperous community. Using ethnographic data obtained from selected members of the ICGC, this article investigates the idea and the implementation of the development plan, in order to understand the plan as Otabil’s conscious effort to change society through the transformation of individuals. It argues that Otabil’s efforts can be analysed as a form of religious engineering, where, the individual members are invited to act as engineers of their own life and subjectivity.
free
Keywords: African Pentecostalism; Prosperity gospel; religion and development; religious engineering